Yu yi ruan jian she ji = Semantic software design / = Semantic software design - Hewitt, Eben (Zhongguo dian li chu ban she = China Electric Power Press, 2022)
Detailed summary in vernacular field.
880-04;"O'Reilly Media, Inc. shou quan Zhongguo dian li chu ban she chu ban.". - Includes bibliographical references
Keywords: Computer software -- Development -- Management; Software architecture; Architecture logicielle